Polymorphous low-grade adenocarcinoma: a case report - Potluri, A (The British Institute of Radiology., 2013)
We present a case of de novo polymorphous low-grade adenocarcinoma (PLGA) arising in a minor salivary gland with a relatively large radiographic extent compared with that of most of the PLGAs reported. This paper describes the radiographic extent of the lesion and the findings of CT imaging.